Ecological Education as a Factor of Increase of Ecological Consciousness Level of Students - Леонід Виговський; Tatiana Vygovs’ka (Pedagogical Discourse, 2012)
Ecological education as a factor of ecological consciousness formation of students is considered. Three levels of maturity of ecological consciousness are distinguished for students: naively-realistic, ordinary-empiric and consciously-theoretical. The ways of forming of ecological consciousness of students during teaching and educational process are analized